Leisure-time physical activity among women in a neighbourhood in Bogotá, Colombia: prevalence and socio-demographic correlates (2004)
ABSTRACT: This study measured the prevalence of leisure-time physical activity in women from 18 to 69 years of age and identified correlated social factors in the neighborhood of Santafe, Bogotá, Colombia. Levels of physical activity were calculated through a population survey (n = 1,045). Logistic regression modeling identified factors associated with inactivity. Some 79.1% of respondents reported being inactive; 15.7% practiced physical exercise irregularly; and 5.2% regularly practiced physical exercise. After adjustment of covariates, physical inactivity was associated with not participating in recreational weekend activities on Sundays and not planning to lose weight. The results of this study show the high proportion of physically inactive women in a community in Bogotá Intervention strategies should be developed to reinforce recreational weekend activities on promoted by the Municipality.